2014
DOI: 10.1089/gtmb.2014.0030
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of FokI Polymorphism of Vitamin D Receptor Gene in Intervertebral Disc Degeneration

Abstract: The results showed a positive association between VDR FokI/T2C polymorphism and DD in Brazilian patients tested.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 31 publications
1
34
0
2
Order By: Relevance
“…Vitamin D receptor 28,29,33,36,44,46,61,63,90,93,94,97,102,103,113) VDR has an important role in normal bone mineralization and bone remodeling. It has been reported that the polymorphism of VDR contributes to diseases, such as osteoporosis, osteoarthritis, and LDDs.…”
Section: Matrix Metalloproteinase-3 and Other Mmpsmentioning
confidence: 99%
See 1 more Smart Citation
“…Vitamin D receptor 28,29,33,36,44,46,61,63,90,93,94,97,102,103,113) VDR has an important role in normal bone mineralization and bone remodeling. It has been reported that the polymorphism of VDR contributes to diseases, such as osteoporosis, osteoarthritis, and LDDs.…”
Section: Matrix Metalloproteinase-3 and Other Mmpsmentioning
confidence: 99%
“…It has been reported that the polymorphism of VDR contributes to diseases, such as osteoporosis, osteoarthritis, and LDDs. Numerous studies have focused on the relationship between the polymorphisms of VDR with or without other genes and LDDs 28,29,33,36,44,46,61,63,90,93,94,97,102,103) . All of the studies demonstrated that the t allele of VDR Taq I was associated with a high risk of LDDs.…”
Section: Matrix Metalloproteinase-3 and Other Mmpsmentioning
confidence: 99%
“…(189) Moreover, the recombinant human GDF-5 (rhGDF-5) enhances cell proliferation and matrix synthesis and accumulation by both bovine NP and AF cells. (190) Some epidemiologic studies highlighted that DD may be caused to a large degree by hereditary factors with apparently a relatively minor effects of environmental and behavioral risk factors (191)(192)(193)(194)(195), which indicated that genetic factors might play an important role in the pathogenesis of IDD.…”
Section: Lbp Pathophysiologymentioning
confidence: 99%
“…Over the past two decades, various polymorphisms affecting the expression and function of VDRs in IVDD have been identified. These SNPs include FokI (rs2228570), TaqI (rs731236), and ApaI (rs7975232) (12, 20, 24, 44, 48, 49, 51, 61, 62). …”
Section: Gene Polymorphisms Associated With Ivddmentioning
confidence: 99%
“…The FokI polymorphism of VDR is a C to T substitution found in exon 2 (49). This SNP leads to altered protein size, and subsequently, altered function.…”
Section: Gene Polymorphisms Associated With Ivddmentioning
confidence: 99%